Analisa Pelayanan Kefarmasian Pada PAsien Rawat Jalan Di Depo Farmasi RSUD IBNU SINA Gresik Berdasarkan Waktu TUnggu Pelayanan Resep - Sholikhah, Nur Anisaus; Tiadeka, Pemta; Aisiyah, Siti Nur (Universitas Muhammadiyah Gresik, 2019)
Usually, response time is a waiting time that counts from patient giving prescription until they receive the medicine. Response time colud influence patients satisfied if took a long time to get the medicine. Besides that, those phenomena could decrease patient satisfaction dan they will think twice to come back to the hospital. Ibnu Sina Hospital tries to increase the pharmacy service with the observation of response time in Depo Pharmacy Pavilion. The purpose of that observation is to optimized pharmacy service by medicine prescription to dispended medicine prescription. This observation is done by retropective methode from January to March 2018. The result of this observation showed that respon time average for medicine prescription is 26 minutes and the average response time for dispende medicine is 36 minutes. This result is suitable with Phramcacautical Service Standart from Kepmenkes No.129/Menkes/SK/II/2008 about prescription services that said respon time for less medicine prescription is than 30 minutes meanwhile for the other one is less than 60 minutes.